Visualizing the Chain-Flipping Mechanism in Fatty-Acid Biosynthesis - Beld, Joris; Cang, Hu; Burkart, Michael D. (Angewandte Chemie (International ed.), 2014)
The acyl carrier protein (ACP) from fatty acid synthases sequesters elongating products within its hydrophobic core, but this dynamic mechanism remains poorly understood. We exploited solvatochromic pantetheine probes attached to ACP that fluoresce when sequestered. The addition of a catalytic partner lures the cargo out of the ACP and into the active site of the enzyme, thus enhancing fluorescence to reveal the elusive chain‐flipping mechanism. This activity was confirmed by the use of a dual solvatochromic cross‐linking probe and solution‐phase NMR spectroscopy. The chain‐flipping mechanism was visualized by single‐molecule fluorescence techniques, thus demonstrating specificity between the Escherichia coli ACP and its ketoacyl synthase catalytic partner KASII. Flipping out in style: Protein–protein interactions with the partner protein ketoacyl synthase II (KASII) cause fatty‐acid‐intermediate cargo sequestered by the acyl carrier protein (ACP) to flip from the hydrophobic core of the carrier protein into the active site of the partner protein. Solvatochromic pantetheine probes were used to visualize this event (see picture).